2016
DOI: 10.1371/journal.pone.0166599
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Acceptance and Commitment Therapy for Type 2 Diabetes Management: The Moderating Role of Coping Styles

Abstract: Background and AimEvidence of the efficacy of existing psychological interventions for self-management in diabetes is limited. The current study aimed at assessing the effects of group-based ACT on self-management of patients with T2DM, considering the moderating role of coping styles.MethodsOne hundred and six patients with type 2 diabetes were randomly assigned either to the education alone (n = 53) or to a combination of education and group-based acceptance and commitment therapy (n = 53) over a period of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 35 publications
4
65
0
22
Order By: Relevance
“…Of the other outcomes studied, significant changes were found in perceived stress [59] and guilt. Additionally, ACT-related processes, which include acceptance, mindfulness, and values, were measured in two studies, both of which found significant improvements post-intervention compared to the control group [38, 63]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the other outcomes studied, significant changes were found in perceived stress [59] and guilt. Additionally, ACT-related processes, which include acceptance, mindfulness, and values, were measured in two studies, both of which found significant improvements post-intervention compared to the control group [38, 63]. …”
Section: Resultsmentioning
confidence: 99%
“…Of the four studies that measured HBA1C, only one found significant reductions post-intervention [63]. One study that did not find a significant reduction in HBA1C post-intervention did find a significant decrease in number of participants with an HBA1C below 7.0 [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In domains E and F, the items refer to coping with the disease, addressing the acceptance and the condition of learning to live with the consequences of the treatment. The factors that hinder coping with the disease affect the performance of self-care and should, therefore, be identified by the health team 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in A1c from baseline to follow-up were mediated by participants' use of acceptance-based coping and engagement in diabetes self-management behaviors. In the second study, Shayeghian and colleagues randomized 106 adults with type 2 diabetes to a diabetes education only condition or a diabetes education plus ACT intervention 36 . The diabetes education plus ACT intervention consisted of ten sessions over a three-month period, while adults in the diabetes education only group participated in a 2-h workshop on diabetes control 36 .…”
Section: Standard Behavioral Interventions Are Foundational For Diabementioning
confidence: 99%